(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article is devoted to the study of the issue of climate change in Uzbekistan in the context of global climate change in the world. Currently, the most vulnerable part of nature and society has become the process of climate change at the present stage. An analysis of the causes of climate change in general throughout the world and in the territory of Uzbekistan and its possible consequences in the modern world is given. The article also considers the possible influx of climate migrants in all countries, including Uzbekistan, due to climate change.